Papillary Thyroid Carcinoma: Molecular Distinction by MicroRNA Profiling - Galuppini, Francesca; Censi, Simona; Merante Boschin, Isabella; Fassan, Matteo; Sbaraglia, Marta; Valeri, Nicola; Hahne, Jens Claus; Bertazza, Loris; Munari, Giada; Galasso, Marco; Cascione, Luciano; Barollo, Susi; et al. (Frontiers in Endocrinology, 2022)
Papillary thyroid carcinoma (PTC) is a miscellaneous disease with a variety of histological variants, each with its own mutational profile, and clinical, and prognostic characteristics. Identification of microRNA (miRNA) expression profiles represents an important benchmark for understanding the molecular mechanisms underlying the biological behavior of these unique PTC subtypes in order that they be better characterized. We considered a series of 35 PTC samples with either a histological diagnosis of hobnail (17 cases) or classical variant (nine cases), and with a specific BRAF p.K601E mutation (nine cases). We determined the overall miRNA expression profile with NanoString technology, and both quantitative reverse transcription–PCR and in situ hybridization were used to confirm selected miRNAs. The miRNA signature was found to consistently differentiate specific histotypes and mutational profiles. In contrast to the BRAF p.K601E mutation and classic PTCs, three miRNAs (miR-21-5p, miR-146b-5p, and miR-205-5p) were substantially overexpressed in the hobnail variant. The current study found that different miRNA signature profiles were linked to unique histological variants and BRAF mutations in PTC. Further studies focusing on the downstream pathogenetic functions of mRNAs in thyroid neoplasms are warranted.